Assessment of employee engagement in the implementation of an employee suggestion program in company x: Research results - Damian Ostrowski (Economic and Environmental Studies (E&ES), 2017)
One of the most frequently implemented tools in Polish enterprises, which arises from the Lean Management concept, here understood in its broader sense, are so called schemes of employee suggestion. Their primary objective is to activate (motivate) employees of a specific enterprise to share their ideas, suggestions which could influence the improvement of an organization. Programs of this type which operate efficiently are also the answer to the eighth type of waste, according to the categories proposed by T. Ohno - not capitalizing on employees' creativity. The programs represent a cohesive element in the broad idea of employee participation in organization management. This paper presents the findings of a survey on the perception and involvement of employees working for a specific enterprise in the functioning of an employee suggestion scheme.
Keywords: M11; M12; 330; employee suggestion system; Kaizen; continuous improvement concept